(untitled) (Research, Society and Development, 2022)
This study aims to analyze class diaries written by one of the authors during the years 2014 and 2015 during the Supervised Internship in the English Language at the Federal University of Santa Maria. The writings narrate the school routine and the class events weekly as the teacher of a sixth-year elementary school class in a public school during her first experience as a teacher. This research seeks to reflect on the (auto)biographical process in teacher education and the reflections of documentation, dissemination, and reading of private narratives. Using the qualitative approach of an (auto) biographical nature as a method, the narratives were analyzed through semantic appreciation and grouped into categories, called formative scenarios, through recurrences in the discourse. Four categories were identified: family, politics and ideology, frustration, and social ills. The research is theoretically supported by studies by Bertaux (2010), Ferraroti (2014), Larossa (2008), Passeggi (2011), and Rodrigues and Prado (2015), among others. It was found that self-narratives have a reflective and formative function for researchers, research subjects, and readers and that this formation has a non-linear and intermittent character along personal and professional trajectories. It was also understood that confessional documents, more than a singular representation of a single subject, also have social historical value when dealing with a certain space/time and context. Thus, it was found that self-narratives have the potential to consolidate themselves as academic knowledge, transforming experiences and experiences narrated by the subject into theory.